ANALISIS PERENCANAAN PAJAK PENGHASILAN PASAL 21 SEBELUM DAN SESUDAH BERLAKUNYA PMK NOMOR 66 TAHUN 2023 PADA PT CPN - Nanda Marini Olga Griselda Baitanu; Norbertus Purnomo Lastu; Levi Martantina (Jurnal Bisnis Terapan, 2025)
Tax planning is an effort to reduce or minimize the tax burden that must be paid to the state, ensuring that the tax paid does not exceed the actual amount while still complying with applicable tax regulations, hence legal. The change in regulations, namely PMK Number 66 of 2023, is interesting to analyse because it directly impacts employees and companies, particularly in designing more strategic and efficient tax planning strategies. This study aims to analyse the planning of Income Tax (PPh) Article 21 at PT CPN before and after the implementation of the Minister of Finance Regulation (PMK) Number 66 of 2023. The method used in this research is a descriptive method with a qualitative approach at PT CPN using observation and documentation techniques. The data analysed includes financial reports, tax documents, and interviews with related parties at PT CPN. This analysis aims to evaluate the impact of the new regulation on the company's tax burden and identify changes in the strategies implemented. The results of the study show that the Minister of Finance Regulation (PMK) Number 66 of 2023 has a significant impact on PT CPN's tax planning. This research found that tax planning conducted after the implementation of the Minister of Finance Regulation (PMK) Number 66 of 2023 is more efficient. Additionally, this research identifies the challenges faced by PT CPN in adjusting to the new regulation and provides recommendations for optimizing future tax planning.